Reverse logistics network design: A holistic life cycle approach - Joanna Daaboul; Julien Le Duigou; Diana Penciuc; Benoît Eynard (Journal of Remanufacturing, 2014)
When aiming for a more sustainable world, enterprises such as aircraft and automobile industries are highly interested in lightweight components and solutions. Among these solutions are aluminum wrought alloys that offer high potentials for dramatic weight reduction of structural parts. Nevertheless, the production of virgin aluminum is highly energy consuming. Major energy reduction may be achieved if recycled aluminum is used. The aim of the European project SuPLight is to address new industrial models for sustainable lightweight solutions - with recycling in high-end structural components based on wrought alloys. This article addresses the issue of designing the reverse logistics network assuring the needed volume of recycled aluminum for the production of L-shaped front lower control arms for personal cars. It details the developed method and demonstrator for designing a reverse logistics network based on a life cycle assessment.
Keywords: 650; Reversed logistics design; LCA; Wrought aluminum